Linking self-rated social inclusion to social behaviour - Schwab, Susanne; Gebhardt, Markus; Krammer, Mathias; Gasteiger-Klicpera, Barbara (Technische Universität Dortmund, 2015)
Successful inclusive education creates a learning environment that supports not only the cognitive abilities of all children but also their social and emotional development. The present study focuses on the development of social participation of students with and without special education needs (SEN). A longitudinal study with two measurement times was conducted. The first measurement (T1) took place at the end of 5th grade, the second (T2) one year later. The sample consisted of 35 SEN students and108 Non-SEN students from mainstream classes in Graz, Austria. For assessing the self-perception of social inclusion, Items from the “dimensions of integration” questionnaire (FDI 4-6; Haeberlin, Moser, Bless and Klaghofer 1989) were used. Social participation does not seem to be a very stable phenomenon; its retest reliability was only .47 for SEN students and .54 for Non-SEN students. Results indicate that children with SEN experienced less social participation than children without SEN at T1 and T2. To identify the predictors for social participation, a multiple regression analysis was conducted. Next to social participation at T1, indirect aggressive behaviour (self-assessed) also appears to predict social participation at T2.
an empirical study of students with and without special education in secondary schools
Keywords: Social participation; Inclusion; Longitudinal study; Social behaviour; Students with special needs; Mainstream schools; 370; Sonderpädagogik; Förderunterricht; Inklusion; Partizipation; Sozialverhalten; Österreich